NON-PERMANENT MEMBERSHIP IN THE UN SECURITY COUNCIL AND REGIONAL AGENDA PROMOTION: VARIATION IN REGIONAL REPRESENTATION - Birzhanova, Dina (Nazarbayev University School of Sciences and Humanities, 2018)
This research complements existing quantitative literature on the role of the non-permanents members in the UNSC. In particular, the research analyzes to what extent the UNSC non-permanent members successfully promote their regional agendas as regional representatives. Moreover, this analysis in its turn tries to reveal an important theoretical concern such as the ability of the less powerful states (non-permanent members) to have influence on the most powerful (the P5). In the framework of this research the regional agenda promotion is considered as raising international attention on regional security issues and increasing the number of peacekeepers deployed to the established UN missions. Analysis of the effect of regional representation on both dimensions of regional agenda promotion is supplemented with analysis of a regional representative’s individual characteristics. The latter constitutes factors of opportunity and willingness that encourage or discourage a non-permanent member to promote its region’s agenda.
БҰҰ ҚАУІПСІЗДІК КЕҢЕСІНДЕГІ ТҰРАҚТЫ ЕМЕС МҮШЕЛІК ЖӘНЕ АЙМАҚТЫҚ КҮН ТӘРТІБІН ІЛГЕРІЛЕТУ: АЙМАҚТЫҚ ӨКІЛДІКТЕГІ ВАРИАЦИЯ
НЕПОСТОЯННОЕ ЧЛЕНСТВО В СОВЕТЕ БЕЗОПАСНОСТИ ООН И ПРОДВИЖЕНИЕ РЕГИОНАЛЬНОЙ ПОВЕСТКИ ДНЯ: ВАРИАЦИЯ В РЕГИОНАЛЬНОМ ПРЕДСТАВИТЕЛЬСТВЕ
Keywords: UN security council